Characteristics of soil microbiota and organic carbon distribution in jackfruit plantation under different fertilization regimes - Su, Lanxi; Bai, Tingyu; Wu, Gang; Zhao, Qingyun; Tan, Lehe; Xu, Yadong (Frontiers in Microbiology, 2022)
Manure amendment to improve soil organic carbon (SOC) content is an important strategy to sustain ecosystem health and crop production. Here, we utilize an 8-year field experiment to evaluate the impacts of organic and chemical fertilizers on SOC and its labile fractions as well as soil microbial and nematode communities in different soil depths of jackfruit (Artocarpus heterophyllus Lam.). Three treatments were designed in this study, including control with no amendment (CK), organic manure (OM), and chemical fertilizer (CF). Results showed that organic manure significantly increased the abundance of total nematodes, bacterivores, bacteria and fungi as well as the value of nematode channel ratio (NCR) and maturity index (MI), but decreased plant-parasites and Shannon diversity (H′). Soil microbial and nematode communities in three soil depths were significantly altered by fertilizer application. Acidobacteria and Chloroflexi dominated the bacterial communities of OM soil, while Nitrospira was more prevalent in CF treatment. Organic manure application stimulated some functional groups of the bacterial community related to the C cycle and aprotroph-symbiotroph fungi, while some groups related to the nitrogen cycle, pathotroph-saprotroph-symbiotroph and pathotroph-saprotroph fungi were predominated in CF treatment. Furthermore, organic manure enhanced the soil pH, contents of total soil N, P, K, and SOC components, as well as jackfruit yield. Chemical fertilizers significantly affected available N, P, and K contents. The results of network analyses show that more significant co-occurrence relationships between SOC components and nematode feeding groups were found in CK and CF treatments. In contrast, SOC components were more related to microbial communities than to nematode in OM soils. Partial least-squares-path modeling (PLS-PM) revealed that fertilization had significant effects on jackfruit yield, which was composed of positive direct (73.6%) and indirect effects (fertilization→fungal community→yield). It was found that the long-term manure application strategy improves soil quality by increasing SOM, pH, and nutrient contents, and the increased microbivorous nematodes abundance enhanced the grazing pressure on microorganisms and concurrently promoted microbial-derived SOC turnover.